The Impact of Polyethylene Glycol-Modified Chitosan Scaffolds on the Proliferation and Differentiation of Osteoblasts - Tsai, Wei-Bor; Ahmed, Ibrahim Nasser (International Journal of Biomaterials, 2023)
The objective of this study was to investigate the influence of polyethylene glycol (PEG) incorporated chitosan scaffolds on osteoblasts proliferation and differentiation. The chitosan polymer was initially modified by the predetermined concentration of the photoreactive azido group for UV-crosslinking and with RGD peptides (N-acetyl-GRGDSPGYG-amide). The PEG was mixed at different ratios (0, 10, and 20 wt%) with modified chitosan in 96-well tissue culture polystyrene plates to prepare CHI-100, CHI-90, and CHI-80 scaffolds. PEG-containing scaffolds exhibited bigger pore size and higher water content compared to unmodified chitosan scaffolds. After 10 days of incubation, the cell number of CHI-90 (1.1 × 106 cells/scaffold) surpasses that of CHI-100 (9.2 × 105 cells/scaffold) and the cell number of CHI-80 (7.6 × 105 cells/scaffold) were significantly lower. The ALP activity of CHI-90 was the highest on the fifth day indicating the favored osteoblasts' early-stage differentiation. Moreover, after 14 days of osteogenic culture, calcium deposition in the CHI-90 scaffolds (2.7 μmol Ca/scaffold) was significantly higher than the control (2.2 μmol Ca/scaffold) whereas on CHI-80 was 1.9 μmol/scaffold. The results demonstrate that PEG-incorporated chitosan scaffolds favored osteoblasts proliferation and differentiation; however, mixing relatively excess PEG (≥20% wt.) had a negative impact on osteoblasts proliferation and differentiation.